PREDICTING THE OUTCOME OF THE DISEASE IN CHILDREN WITH ACUTE RESPIRATORY VIRAL INFECTIONS COMPLICATED BY PNEUMONIA - Sayfiddinov Ulmas Sirozhiddin ugli; Pulatova Shakhnoza Khaidarovna (World Scientific Research Journal, 2025)
Summary: Acute respiratory viral infections (ARVI) are a broad class of diseases caused by viruses that infect the upper and lower respiratory tracts. SARS is one of the most common causes of children going to pediatricians, and in some cases, the infection can be complicated by more serious conditions, such as pneumonia. Pneumonia, in turn, is one of the leading causes of hospitalization and mortality among children, especially in infancy and early childhood. Predicting the outcome of the disease in children with acute respiratory viral infections complicated by pneumonia is an important task that requires a comprehensive approach and consideration of many factors.